FINANCING AND QUALITY OF HOUSING CONSTRUCTION: INTRODUCTION OF INFORMATION SYSTEMS AS A REGULATORY TOOL - Fedorova, Irina; Urunov, Asror; Rodina, Irina; Ostapenko, Vladislav (Revista Inclusiones, 2020)
Housing construction is one of the most important areas of construction, which not only provides normal living conditions for the population but also contributes to improving their quality in general. Housing construction plays an important role in the socio-economic development of the country as a powerful source of the multiplier effect to stimulate related industries by solving social problems and expanding investment opportunities for the population. The article analyzes the scientific literature on the problem of regulating the activities of participants and the introduction of information systems in the field of housing construction.